2012
DOI: 10.1002/jbm.a.34218
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane modified with an antithrombin‐heparin complex via polyethylene oxide linker/spacers: Influence of PEO molecular weight and PEO‐ATH bond on catalytic and direct anticoagulant functions

Abstract: A segmented polyurethane (PU) was modified with polyethylene oxides (PEO) of varying molecular weight and end group. The PEO served as linker/spacers to immobilize an antithrombin-heparin (ATH) anticoagulant complex on the PU. Isocyanate groups were introduced into the PU to enable attachment of either "conventional" homo-bifunctional dihydroxy-PEO (PEO-OH surface) or a hetero-bifunctional amino-carboxy-PEO (PEO-COOH surface). The PEO surfaces were functionalized with N-hydroxysuccinimide (NHS) groups using ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…These include gold-thiol reactions 151 and isocyanate-hydroxyl reactions 153 to attach PEO to the substrate, and N-hydroxysuccinimide (NHS)-hydroxyl reactions to attach ATH to the distal end of the PEO. 154 These ATH-PEO surfaces showed improved antithrombotic activity (antithrombin binding, factor Xa inhibition, prolonged clotting time, reduced platelet adhesion). Interestingly it was found that the protein This journal is © The Royal Society of Chemistry 2014 resistance of the PEO was not diminished by the closely adjacent ATH.…”
Section: Bioactive Surfacesmentioning
confidence: 96%
See 1 more Smart Citation
“…These include gold-thiol reactions 151 and isocyanate-hydroxyl reactions 153 to attach PEO to the substrate, and N-hydroxysuccinimide (NHS)-hydroxyl reactions to attach ATH to the distal end of the PEO. 154 These ATH-PEO surfaces showed improved antithrombotic activity (antithrombin binding, factor Xa inhibition, prolonged clotting time, reduced platelet adhesion). Interestingly it was found that the protein This journal is © The Royal Society of Chemistry 2014 resistance of the PEO was not diminished by the closely adjacent ATH.…”
Section: Bioactive Surfacesmentioning
confidence: 96%
“…We have developed ATH as a surface modier using gold, 151,152 polyurethane 153,154 and PDMS 155 as substrates. The ATH was attached to these substrates using PEO as a spacer and for protein resistance.…”
Section: Bioactive Surfacesmentioning
confidence: 99%
“…11,12 There are numerous reports on polyurethane surface modification for decreased protein adsorption and cell adhesion. [13][14][15][16][17][18][19][20][21][22][23][24] Some are focused on making entire hydrophilic or amphiphilic polyurethane polymers before forming a medical device 24 but some are focused on surface modification of the formed medical device. [13][14][15][16][17][18][19][20][21][22][23] Generally speaking, interface between medical implant device and body fluid or tissue play a key role in biocompatibility of medical device.…”
Section: Introductionmentioning
confidence: 99%
“…15 There are many reports on modification of polyurethane for reduced protein adsorption and cell adhesion. [16][17][18][19][20][21][22][23][24][25][26][27][28] Some are focused on making entire hydrophilic or amphiphilic polyurethane polymers before forming a medical device 28 but some are focused on surface modification of the polyurethane formed medical device. [16][17][18][19][20][21][22][23][24][25][26][27] Regarding bacterial infection prevention, currently, there exist three strategies in developing antibacterial surfaces.…”
Section: Introductionmentioning
confidence: 99%